Systems information modelling: Enabling digital asset management. (December 2016) - Love, Peter E.D.; Zhou, Jingyang; Matthews, Jane; Luo, Harbin
Highlights: The quality of 'As-built' information documented using Computer Aided Design (CAD) for a rail infrastructure project is evaluated. The extent of errors, omission and information redundancy is quantified. A system information model that is object oriented is retrospectively developed based on the CAD documentation. It is empirically demonstrated that a SIM an provide significant productivity and cost benefits. Provides the foundation for a use case for Digital Asset Management for infrastructure projects. Abstract: Having access to the right information at the right time has been, and remains a pervasive problem during operations and maintenance (O&M) and thus hinders an asset owner's ability to ensure their facilities performance are being optimized. Typically, asset managers are often confronted with 'As-built' documentation that is prepared using Computer-Aided-Design (CAD) and is often incomplete, erroneous and/or redundant, which adversely impacts an asset's integrity and productivity during O&M. With this mind, the quality of information contained within 'As-Built' electrical documentation for an 'Underground Railway Station' is evaluated by quantifying the errors and omissions contained within them. The cost to document information using CAD compared to the development of a System Information Model (SIM) is determined. A retrospective SIM is constructed and a bi-directional link with a three dimensional (3D) model is established to ensure the integrity of the information required for O&M. The use of a SIM instead of CAD can provide engineers with a new medium and process for preparing the design and documentation of electrical systems as it provides them with an ability to obtain significant productivity and cost benefits. The empirical research presented in this paper provides the impetus for future research in the fertile and unexplored area of Digital Asset Management for infrastructure projects.